1993
DOI: 10.1177/074823379300900505
|View full text |Cite
|
Sign up to set email alerts
|

Health Status by Social Class and/or Minority Status: Implications for Environmental Equity Research

Abstract: Much of the epidemiologic research in the United States has been based only on the categories of age, sex and race; thus, race has often been used in health statistics as a surrogate for social and economic disadvantage. Few multivariate analyses distinguish effects of components of social class (such as economic level) from the relative, joint, and independent effects of sociocultural identifiers such as race or ethnicity. This paper reviews studies of social class and minority status differentials in health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 86 publications
1
20
0
Order By: Relevance
“…Increasing evidence indicates that disparate environmental and economic conditions have taken their toll on the health of the U.S. Hispanic population (e.g., Mexican Americans) (8)(9)(10)(11)(12). These studies have yielded some very basic facts concerning Hispanics living in the United States.…”
Section: Current Problems Facing the Mexican American Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence indicates that disparate environmental and economic conditions have taken their toll on the health of the U.S. Hispanic population (e.g., Mexican Americans) (8)(9)(10)(11)(12). These studies have yielded some very basic facts concerning Hispanics living in the United States.…”
Section: Current Problems Facing the Mexican American Populationmentioning
confidence: 99%
“…Poverty rates among Hispanics are more than 3 times those of Caucasians in the United States (8), and educational attainment is much lower among Hispanics than among Caucasians (8). Second, Hispanics suffer disproportionate rates of environmentally related morbidity and mortality when compared with more affluent and better-educated populations (9)(10)(11)(12). Third, Hispanics often live in environmentally stressed communities in which environmental hazards in the community are prevalent.…”
Section: Current Problems Facing the Mexican American Populationmentioning
confidence: 99%
“…It is possible, if not likely, that interactions among these three sociodemographic variables are important determinants of systematic differences (e.g., exposure, health status, access to health care) among population subgroups and that these differences may increase a subgroup's susceptibility to the adverse effects of environmental exposures. 2,6,[30][31][32][33] The following discussion is based on data from three diverse areas: the industrialized region of the Kanawha Valley, WV; the industrial corridor along the lower Mississippi River from Baton Rouge to New Orleans, LA; and the greater metropolitan area of Baltimore, MD.…”
mentioning
confidence: 99%
“…This study showed that although there were statistically significant differences between sexes, ethnic groups and schools, the magnitude reported was unlikely to have had clinical or public health significance. Moreover, while the differences between the ethnic groups and the schools could be a reflection of social class [26], other cultural and environmental factors may also have been involved.…”
Section: Discussionmentioning
confidence: 99%